POLA KONSUMSI, KEPUASAN DAN LOYALITAS KONSUMEN DALAM PEMBELIAN LUWAK WHITE KOFFIE DI WARUNG KOPI ANGKRINGAN KOTA BANDAR LAMPUNG - Gustini, Triana Herli; Sayekti, Wuryaningsih Dwi; Adawiyah, Rabiatul (Lampung University, 2024)
This study aimed to determine consumption patterns, satisfaction and consumer loyalty in purchasing Luwak White Koffie in Bandar Lampung. The location for this research was the angkringan coffee shop PKOR Way Halim, Teuku Umar Kedaton street and Taman Gajah Saburai. The total sample was 60 people selected by the probability sampling method which was carried by means of multistage random sampling. The data were analyzed using descriptive analysis methods, Customer Satisfaction Index (CSI) and Customer Loyalty Index (CLI). The results showed that the consumption of Luwak White Koffie consumers in the last month was 6.23 sachets. The consumption frequency of Luwak White Koffie consumers in angkringan coffee shops is 2.37 times/month and at home 3.87 times/month. The flavors that consumers like the most were the original vanilla flavors. Most consumers of Luwak White Koffie consumed coffee at night. The purpose or reason for consumers consuming Luwak White Koffie was because of the taste. The reason consumers choose to buy or consume Luwak White Koffie at angkringan coffee shops was purely coincidental with the assumption that consumers accidentally visited an angkringan coffee shop and consumers drank Luwak White Koffie because consumers liked the taste of the coffee. The Luwak White Koffie's consumer satisfaction was in the very satisfied category with its CSI value of 81.46. The condition of Luwak White Koffie consumer loyalty was in the loyal category with its CLI value of 77.43. Consumers would make repeated purchases of Luwak White Koffie. Key words: consumption pattern, customer behavior, loyalty, satisfaction